Heaven sent - Norhafsah Hamid (Dar Al Wahi Publication, 2017)
Sarah is a Muslim girl faced with challenges and obstacles to remain true to her religion. Whilst she endures hardship, she also found friendship and love. Jonah is the 'modern day' Rome and enjoys the company of women but when he met Sarah, his whole world changed. Both are from different background and religion but yet their path kept crossing. Is it fate or just coincidence?